2019
DOI: 10.22555/joeed.v6i1.2749
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Awareness of Reading Strategies, Reading Practices and Academic Attainments of University Students

Abstract: This study was conducted to examine the relationship between metacognitive awareness of reading strategies (MARS), and academic attainments (AA) of undergraduate business students. It also investigated the relationship between reading practices (RP) and MARS. There are three different categories of MARS-global, problem solving, and support reading strategies. The Metacognitive Awareness of Reading Strategies Inventory (MARSI), developed by Mokhtari and Reichard (2002) was used as the instrument for this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The researcher concluded that the more problem-solving strategies are used during the reading process, the better understanding of the texts the students show. Also, Irfan et al (2019) found that students' understanding of MCRS is a robust predictor of their academic progress. Other studies indicated a significant improvement in students' outcomes after being trained in MCRS (Thongwichit & Buripakdi, 2021;Wu et al, 2021).…”
Section: Metacognitive Strategies and Reading Comprehensionmentioning
confidence: 92%
See 1 more Smart Citation
“…The researcher concluded that the more problem-solving strategies are used during the reading process, the better understanding of the texts the students show. Also, Irfan et al (2019) found that students' understanding of MCRS is a robust predictor of their academic progress. Other studies indicated a significant improvement in students' outcomes after being trained in MCRS (Thongwichit & Buripakdi, 2021;Wu et al, 2021).…”
Section: Metacognitive Strategies and Reading Comprehensionmentioning
confidence: 92%
“…For example, Gebhard (2000) reported a statistically significant correlation between the participants' use of MCRS and their reading comprehension scores and that skilled readers who employed MCRS effectively scored higher in reading comprehension tests than the struggling ones. Research also demonstrated that learning MCRS facilitates L2 acquisition (Ahmadi et al, 2013), and improves reading comprehension scores (Irfan et al, 2019;Par, 2020;Sutiyatno & Sukarno, 2019;Thongwichit & Buripakdi, 2021;Villanueva, 2022;Wu et al, 2021). Sutiyatno and Sukarno (2019), for instance, found an association between undergraduate students' reading performance and their use of metacognitive strategies.…”
Section: Metacognitive Strategies and Reading Comprehensionmentioning
confidence: 96%
“…In addition, reading practice and how often the dyslexic child is trained to read. In reading skills, the most crucial element so that children can read quickly is practice (Irfan et al, 2019;Solmaz, 2020). If not, then the child will experience difficulty in reading skills.…”
Section: Graph 1 Reading Development Of Dyslexic Childrenmentioning
confidence: 99%
“…However, the teacher is the most vital and dominant component in teaching and learning activities. Teachers have the role as planners and implementers of learning and motivation to encourage students to do learning assignments (Irfan et al, 2019;Fauzan et al, 2022). This indicates the urgency of educators in the world of education, whose job is to teach and as motivators and facilitators in learning activities (Aboagye & Yawson, 2020).…”
Section: Introductionmentioning
confidence: 99%